2012
DOI: 10.1007/s00114-012-0978-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype differences in Drosophila are enhanced by semi-natural conditions

Abstract: Morning and evening chronotypes of sleep/wake cycles in humans are often metaphorically termed as 'larks' and 'owls'. We derived Drosophila populations early and late, displaying lark- and owl-like emergence chronotypes by imposing selection for adult emergence during morning and evening hours. Preference for morning and evening emergence in these populations was accompanied by divergence in their circadian period (τ) and photic phase response curve. To test if lark- and owl-like emergence chronotypes displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Out-of-phase cycles of light and temperature (ALTC2 and SLTC2) also employed the combined waveforms of light and temperature as in ALTC1 and SLTC1, but in these cases, the temperature cycles lagged the light cycles by 4 h. The rate of increase and decrease of light and temperature cycles, as well as the 4-h phase difference between them, was set to resemble conditions in nature during the month of March 2011 in Bangalore, India (12°59′N 77°35′E), as reported in Vaze et al (2012a), where a large difference in phase of emergence was first reported. In both SLC and STC, ExT06 marks the onset of stepwise light/temperature increase, and offset of stepwise light/temperature decrease in the evening is marked by ExT18.…”
Section: Adult Emergence Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Out-of-phase cycles of light and temperature (ALTC2 and SLTC2) also employed the combined waveforms of light and temperature as in ALTC1 and SLTC1, but in these cases, the temperature cycles lagged the light cycles by 4 h. The rate of increase and decrease of light and temperature cycles, as well as the 4-h phase difference between them, was set to resemble conditions in nature during the month of March 2011 in Bangalore, India (12°59′N 77°35′E), as reported in Vaze et al (2012a), where a large difference in phase of emergence was first reported. In both SLC and STC, ExT06 marks the onset of stepwise light/temperature increase, and offset of stepwise light/temperature decrease in the evening is marked by ExT18.…”
Section: Adult Emergence Assaymentioning
confidence: 99%
“…Although these studies have revealed several interesting and unexplored aspects of circadian rhythms that remained masked under standard laboratory conditions, they have only managed to convince us about the complexity of the circadian clock-zeitgeber interaction, failing to provide further insights into the nature of such interactions. Vaze et al (2012a) reported that environmental cycles in nature considerably enhanced chronotype differences between the morning ( early ) and evening ( late ) selected populations of D. melanogaster compared to standard laboratory condition. Adding to the enhanced chronotype differences, emergence rhythms of the early and late populations also exhibited significant reduction in gate widths in SN, suggesting a causal role of multiple zeitgebers in modulating the emergence waveform.…”
mentioning
confidence: 99%
“…A previous study from our laboratory found that the phase divergence between early and late stocks was enhanced under semi-natural conditions wherein the culture vials were exposed to multiple zeitgebers, predominantly light and temperature (Vaze, Kannan, et al, 2012). This prompted us to hypothesize that temperature plays an important role in phase divergence in the context of the aforementioned model of circadian organization.…”
Section: Introductionmentioning
confidence: 99%
“…c) (Kumar et al , ; Nikhil et al , ). Furthermore, it was observed that this divergence was enhanced greatly under semi‐natural conditions (Vaze et al , ) and this was eventually shown to be driven primarily by temperature cycles (Nikhil et al , ), thereby indicating the evolution of a more fundamental clock feature, common to both light and temperature entrainment, that drives the timing of behaviour.…”
Section: Evidence From Laboratory Selection Studiesmentioning
confidence: 99%